Saúde bucal em gestantes: Percepção e aspectos clínicos subsidiando ações no serviço - Angélica Maria Cupertino Lopes Marinho (2015)
The pregnant dentistry assistance, seems still be realized at a incipient way and it’s important that this kind of assistance occurs according to protocols. This study aimed to perform data analysis once collected in the city of Matozinhos/MG so that they were converted into instruments to improve the oral health status of pregnant women. They evaluated caries and periodontal, by only calibrated professional (Cohen Kappa coefficients equal to 0.94, 0.75 and 0.65 for decay, Community Periodontal Index - CPI and Attachment Loss Index Periodontal – PIP, respectively) features sociodemographic, autoperception and access to the service using the criteria of the SB Brazil program. Pregnant women’s perceptions were evaluated before and after operative groups. Besides analyzing statistically, the DMFT index dichotomized by the median value was associated to the family incomes, the perception of treatment necessity and the perception of health provided by the Pearson’s ChiSquare and linear trend Chi-square. McNemar’s Chi-Square tests were used for comparisons before and after educational intervention. The significance level adopted was p<0.05. The DMFT was 12.00 (±6.33), being teeth cavities representing 52.2%. Most of the pregnant women presented some level of periodontal disease or calculus. Dental caries has not been associated with family incomes (p=0.469), need for dental treatment (p=0.161), nor with health perception (p=0.506). The pregnant women in public covered in the study had care needs in relevant oral health and simultaneously ignorance and fears about prenatal dental approach, but after the educational activities , there was improvement in these perceptions (p˂0.01 ). This information, built up an article submitted to the journal and draft of educational brochure on oral health. The version of the brochure, is an important resource for the democratization of health information and must still be validated externally by quantitative and qualitative methods. It could be noted, given the lack of context and high oral health rates among pregnant women, the need to increase the participation of the dentist in the team of prenatal professionals.